'Having a thick skin is essential': mental health challenges for young apprentices in Australia. (16th March 2021) - Einboden, Rochelle; Choi, Isabella; Ryan, Rose; Petrie, Katherine; Johnston, David; Harvey, Samuel B.; Glozier, Nicholas; Wray, Alexis; Deady, Mark
ABSTRACT: Apprenticeships are a common pathway for young people transitioning from education to employment, and adolescence to adulthood. Apprenticeships have undergone considerable reform, and since the 1990s labour market priorities in Australia have resulted in weakening of protections offered to workers through the award system and trade unions. At the same time, mental health issues have increased, with young people carrying a disproportionate burden. The aim of this study was to explore challenges that young apprentices in urban Australian settings face in relation to their mental health. Focus groups were conducted with 54 apprentices, who described a pervasive sense of disposability and poor working conditions as the main challenges to their mental health. These conditions included long work hours, low wages, job insecurity, poor quality education, unrealistic expectations, workplace hierarchies and bullying. Amidst social and economic precarity, apprentices resigned themselves to silently endure poor treatment in their work placements. Findings from this study are especially troubling because, as young people, apprentices simultaneously face a series of life transitions that require support and guidance. This paper brings attention to the workplace conditions that may contribute to young apprentices' vulnerability to mental health problems, highlighting possibilities for structural changes led by policy reform.